2016
DOI: 10.1126/sciadv.1501768
|View full text |Cite
|
Sign up to set email alerts
|

Experimental river delta size set by multiple floods and backwater hydrodynamics

Abstract: Experimental delta lobe size is controlled by bed adjustment to transient floods within the backwater zone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
189
6

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(220 citation statements)
references
References 45 publications
25
189
6
Order By: Relevance
“…It has been observed in many natural deltas that flows below flood conditions are able to transport sediment loads. Ganti et al () ran experiments with a single intermittency value where sediment concentrations were varied in order to yield the same transport slope during low flows and high flows, producing a delta that was not erosive with a constrained topset slope. However, these experiments also simply the reality of the nonlinear sediment transport, where lower flows will generally have smaller sediment concentrations and conversely higher flows will generally have greater concentrations (van Rijn, ), suggesting that variable flow conditions can cause a system to transition from aggradations to erosional as overserved in the presented experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed in many natural deltas that flows below flood conditions are able to transport sediment loads. Ganti et al () ran experiments with a single intermittency value where sediment concentrations were varied in order to yield the same transport slope during low flows and high flows, producing a delta that was not erosive with a constrained topset slope. However, these experiments also simply the reality of the nonlinear sediment transport, where lower flows will generally have smaller sediment concentrations and conversely higher flows will generally have greater concentrations (van Rijn, ), suggesting that variable flow conditions can cause a system to transition from aggradations to erosional as overserved in the presented experiments.…”
Section: Discussionmentioning
confidence: 99%
“…The discharge fluctuations in these experiments were important for limiting vegetation colonization and maintaining the distributary network of the delta. Also, Ganti et al () investigated the role of backwater hydraulics on river delta size by comparing experimental deltas produced with constant discharge with one produced over multiple flood cycles with I = 0.27, where sediment and water discharge values were selected to maintain constant transport slopes between high‐ and low‐flow events. Their experiments showed that deltas with constant discharge conditions were not affected by backwater hydraulics, while the delta with multiple floods produced a deposit with a characteristic delta lobe size that was dependent on the backwater conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Piper et al, 1990)arguably different from the unvegetated deltaic plains of our experiments where longitudinal slopes are on the order of 10 À2 (Figure 6). Martin et al, 2009;Wickert et al, 2013;Kleinhans et al, 2014b;Ganti et al, 2016). Martin et al, 2009;Wickert et al, 2013;Kleinhans et al, 2014b;Ganti et al, 2016).…”
Section: Experimental Delta Morphology and Evolutionmentioning
confidence: 99%
“…Generally, the evolution of river deltas comprises the abandonment of old delta lobes and creation of new (active) delta lobes due to river avulsion (Ganti et al, ; Jerolmack & Swenson, ). The growth of the active river delta lobes is further shaped by the competing fluvial and marine forcings (Galloway, ).…”
Section: Introductionmentioning
confidence: 99%
“…Additional factors such as sediment grain size (Caldwell & Edmonds, ; Orton & Reading, ), vegetation (Nardin et al, ), and the unsteadiness of river discharge (Shaw & Mohrig, ; Wright & Coleman, ) have also been found to play an important role in controlling delta morphodynamics. Regarding the effects of unsteady river discharge on delta morphological evolution, some recent studies have explored the effects of interannual variability of river discharge on delta channel avulsion (Chatanantavet et al, ; Ganti et al, ) and delta growth rate (Rosen & Xu, ). River floods and associated sediment pulses into the delta have been considered as the major factors that affect the growth of delta as well as the supported saltmarsh (Mudd, ; Rosen & Xu, ).…”
Section: Introductionmentioning
confidence: 99%